Análisis de la infraestructura tecnológica gpon en la interconectividad de usuarios de CNT-EP, en la ciudad de Babahoyo - Obando Aliaga, Diana Carolina (2020)
Taking into account the aforementioned, in this research work the need to analyze the GPON technological infrastructure in the interconnectivity of users of the public company National Telecommunications Corporation, Public Company (CNT-EP), in the city of Babahoyo is raised. , in order to know the possibilities of improving the quality of the service that this public company offers in the areas of Mobile Telephony, Fixed Telephony, Broadband, Satellite Television, precisely in the rural sectors. In order to quantitatively assess your satisfaction with the interconnectivity services provided by the state company. This service allows to be more efficient, reducing failures and increasing the data transmission capacity to customers. Finally, the CNT-EP declares that, to the benefit of its clients, all this latest generation technology is applied in its services to guarantee the optimal development of telecommunications in Ecuador: an important advance for our current and future society.